Do changes in the implied volatility of stock options predict future changes in CDS spreads? - Hong, Changsoo; Park, Yuen Jung (Seonmul yeongu (Online), 2025)
This study examines whether changes in the implied volatility of stock options have cross-sectional predictability for future changes in credit default swap (CDS) spreads in the Korean market. The major findings are as follows. First, in the CDS portfolio analysis, when buying a portfolio with the highest increases in implied volatility and selling a portfolio with the highest decreases and rebalancing monthly, the average change in future CDS spreads is positive and statistically significant. Second, the cross-sectional predictive regression analysis shows that the coefficients for changes in implied volatility are significant in most models. The magnitude of the coefficients remains generally stable regardless of the control variables. These findings provide further evidence supporting the perspective of Cao et al. (2023) that increases in implied volatility reflect information about increased default risk due to higher firm value volatility.